The effects of using digital stories and media in foreign language teaching - Karimova, G.; Ishanov, P.; Mukanova, S.; Odintsova, S.; Aratayeva, A. (International Journal of Education in Mathematics, Science, and Technology, 2023)
In Kazakhstan, as in many other countries, foreign language education starts at an early age, but the desired success is not achieved. This may be due to instructional, environmental or socioeconomic factors, as well as cognitive and psychological factors such as the structure of the language, the teaching methods used, and attitudes towards language learning. In language education, digital story activities can play an effective role in the development of students' vocabulary and language skills. In this study, the effects of digital storytelling on English vocabulary and grammar knowledge and attitudes towards the course were examined. This research was conducted experimentally with 70 students from 5th grade of a primary school in Almaty. In this study, which observed the effects of digital storytelling and traditional teaching approaches on vocabulary knowledge, grammar knowledge and attitudes towards the lesson, an experimental research design with control group was used and data were obtained through tests and scales. The findings of the study showed that digital storytelling activities in the experimental group were effective on students' English vocabulary knowledge, grammar knowledge and attitudes compared to the control group in which traditional teaching was applied.
Keywords: media; digital stories; foreign language teaching; Kazakhstan; primary school students